Analysis of the Co-integration Relationship between Concentration and Profitability: An Applied Study on the Jordanian Banking Sector for the Period (2000-2020) - alamro, Hassan; Maaytah, Sulaiman; Aljaafreh, Ali (Jordan Journal of Business Administration, 2024)
This study investigates the relationship of co-integration between concentration and profitability in the Jordanian banking market for the period (2000-2020). The Herfindahl-Hirschman Index (HHI) and the market-share index for the four largest banks (CR4) were used for the following variables (assets, deposits and credit) to represent concentration in the banking sector. In addition, profitability was represented in two indicators: the rate of return on owners’ equity (ROE) and the rate of return on assets (ROA). The study concluded that there is a co-integration relationship between concentration indicators and profitability indicators. There is a negative significant effect of concentration in assets on profitability in the long term and there is a positive significant effect of concentration in deposits and credit on profitability.